Environmental risk modelling and potential sand fly vectors of cutaneous leishmaniasis in Chitral district: a leishmanial focal point of mount Tirich Mir, Pakistan. Issue 9 (27th July 2017) - Zaidi, Farrah; Fatima, Syeda Hira; Jan, Tehmina; Fatima, Mehreen; Ali, Asad; Khisroon, Muhammad; Adnan, Muhammad; Rasheed, Syed Basit
Abstract: Objective: To provide baseline information about suspected vectors and the incidence, distribution and an active zone of transmission for cutaneous leishmaniasis (CL) in Chitral, Pakistan, using GIS tools; and to investigate the role of environmental factors in the disease dynamics. Method: Two surveys in 2014 and 2016 as a basis for choropleth and environmental risk mapping. Results: A total of 769 captured specimens yielded 14 Phlebotomus and six Sergentomyia species including two potential vectors of CL, i.e. Phlebotomus papatasi and Phlebotomus sergenti . P. papatasi (71%) was dominant, followed by P. sergenti (18%). A choropleth map generated in Arcmap 10.1 based on 1560 CL case reports displayed maximum prevalence (0.92–2.5%) in Ayun, Broz, Charun, Chitral 1 and 2 and Darosh 1 and 2 union councils. An environmental risk map constructed by MaxEnt 3.3.3 defined an active zone of transmission based on leishmaniasis occurrence records ( n = 315). The analysis of variable contribution in MaxEnt indicates significance of elevation (54.4%), population density (23.3%) and land use/land cover (6.6%) in CL disease dynamics. Conclusion: The probability of CL increases (0.6–1 on logistic scale) in severely deforested areas, in lowland valleys and in regions with high‐population density.